Contrasting responses of saproxylic beetles and plants to non-native tree invasion reveal feedback mechanisms between trophic levels. (November 2021) - Lanta, Vojtěch; Doležal, Jiří; Kozel, Petr; Hauck, David; Altman, Jan; Kašák, Josef; Foit, Jiří; Šebek, Pavel; Čížek, Lukáš
Abstract: Invasive, alien trees threaten native biodiversity, but detailed information about the patterns and mechanisms of diversity loss remain unknown. We explored the impact of an invasive tree on vascular plants and saproxylic beetles. We compared their species richness, community composition, and selected biological characteristics between stands of invasive black locust ( Robinia pseudoacacia ), a nitrogen-fixing clonal tree, and native oak-dominated, broadleaf forests in the SE Czech Republic and W Slovakia. Compared to native forests, R. pseudoacia stands were characterised by low canopy cover, high light and soil nutrient availability, and similar deadwood volumes. R. pseudoacacia had species-poor, dense understorey vegetation composed of tall, nitrophilous herbs. Saproxylic beetles, on the other hand, were similarly diverse and abundant in both R. pseudoacacia stands and native forests. Their communities were mainly shaped by forest structure, as overall beetle diversity and guilds exploiting more decayed wood benefited from the open canopies and high deadwood volumes. Richness and abundance of threatened plants and beetles requiring fresh wood, together with total richness of threatened beetles were, however, substantially lower in R. pseudoacacia stands. The adverse impacts of R. pseudoacacia on plants partly contrasted with its much less pronounced effects on saproxylic beetles. In intensively exploited landscapes, R. pseudoacacia stands can offer refuge to saproxylic beetles. However their lower diversity and lower incidence of threatened species show that R. pseudoacacia contributes to homogenization and impoverishment of plant and insect assemblages. Robinia stands thus should be eliminated from protected areas and minimalised wherever biodiversity conservation is of concern.